Influence of ACTN3 R577X polymorphism on ventilatory thresholds related to endurance performance - Pasqua, L. A.; Bueno, S.; Artioli, G. G.; Lancha Jr, A. H.; Matsuda, M.; Marquezini, M. V.; Lima-Silva, A. E.; Saldiva, P. H. N.; Bertuzzi, R. (Journal of Sports Sciences, 2016)
The purpose of this study was to verify the association between ACTN3 polymorphism and physiological parameters related to endurance performance. A total of 150 healthy male volunteers performed a maximal incremental running test to determine the speeds corresponding to ventilatory threshold (VT) and respiratory compensation point (RCP). Participants were genotyped and divided into terciles based on the analysed variables. Genotype frequencies were compared through ?2 test between lower and higher terciles, with the lowest or highest values of each analysed variable. ACTN3 XX genotype was over-represented in higher tercile for VT and RCP. Odds ratio also showed significantly higher chances of XX individuals to be in higher tercile compared to RR (7.3) and RR + RX (3.5) for VT and compared to RR genotype (8.1) and RR + RX (3.4) for RCP. Thus, XX individuals could attain the VT and RCP at higher speeds, suggesting that they are able to sustain higher running speeds in lower exercise intensity domains. It could result in higher lipid acids oxidation, saving muscle glycogen and delaying the fatigue during prolonged exercises, which could be the advantage mechanism of this genotype to endurance performance.